Demo and presentation of Digital Mellini Scholar's Workspace - Rodríguez-Ortega, Nuria; Baca, Murtha (My University, 2013)
This paper presents the project "Digital Mellini: Exploring New Tools & Methods for Art-historical Research & Publication", a joint initiative of the Getty Research Institute (Los Angeles) and the University of Málaga (Spain). This paper discusses several aspects and challenges related to the development of digital resources for art-historical research. The main objectives for the Digital Mellini Project are: 1. To explore new methods and tools with which to reinvent the concept of scholarly work and critical publishing in the field of humanities, particularly in the context of art history, in which the convergence of text and image is essential and provides an interesting context for research—a context that has not yet been adequately investigated . 2. To create a methodological model for developing collaborative digital publications that incorporate texts, digital facsimiles, images, computational tools for linguistic analysis and visual communication, and forums for exchanging ideas and sharing knowledge. The ultimate goal is that the international community of specialists can utilize this methodological model and apply to a variety of art-historical projects.
Keywords: Arte - Estudio y enseñanza - Innovaciones tecnológicas; Digital art history; Digital critical edition; Online scholarly workspaces; Digital publications; Digital humanities